Pengaruh Biaya Lingkungan dan Pengungkapan Lingkungan Terhadap Keunggulan Bersaing - Sabarila, Marisa; Sudrajat, Sudrajat; Septiyanti, Ratna (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In conducting their business activities, companies should not only focus on generating profits but also consider the environmental impact caused by their business processes. This is particularly important for companies in the energy sector, which are considered to have a high risk of environmental damage. This study aims to examine the effect of environmental cost and environmental disclosure on competitive advantage. The data used in this study are energy sector companies listed on the Indonesia Stock Exchange for the 2018-2022. Through the purposive sampling method, 37 companies were obtained with a total of 185 observation samples. Based on the result, it was found that environmental cost and environmental disclosure simultaneously affects the competitive advantage proxied by return on invested capital (ROIC). Furthermore, environmental cost negatively affects on competitive advantage and environmental disclosure positively affects on competitive advantage.